The Presentation of the KDI Program and Audience Perception (Oratio Directa, 2018)
This study examines the relationship between the presentation of the Kontes Dangdut Indonesia (KDI) television program on MNCTV and audience perception. An explanatory quantitative design was applied to 75 studio audience members selected from a population of 300 viewers. Data were collected using a questionnaire and analyzed through Pearson product-moment correlation, simple linear regression, and instrument reliability testing. The findings show a positive relationship between program presentation and audience perception, with a correlation coefficient of r = 0.533. The coefficient of determination was R2 = 0.284, indicating that program presentation accounted for 28.4% of the variation in audience perception. The regression equation was Y = 16.325 + 1.004X. The instruments were reliable, with Cronbach’s alpha values of 0.658 for variable X and 0.860 for variable Y.
Keywords: KDI; Audience perception; Television; Program presentation; Quantitative research